Idiopathic gastric perforation in an asplenic infant - Alex Olsen; Leigh McGill (Wolters Kluwer Medknow Publications, 2012)
Introduction: The cause of idiopathic gastric perforations in neonates remains unknown. Perforations of the abdominal oesophagus, stomach and duodenum in infants and children are the rarest type of intestinal perforations. There are 21 reported cases of an idiopathic gastric rupture in non-neonates. Case Report: A 6-week-old boy presented with nausea, vomiting and decreased oral intake. Physical examination revealed a firm, distended abdomen tender. Abdominal lateral decubitus radiograph revealed massive free air. Patient was found to have an idiopathic gastric perforation of the greater curvature with incidental findings of asplenia. Conclusion: Paediatric abdominal foregut perforations have diverse aetiologies. The foregut is the least likely portion of the gastrointestinal tract to perforate in children. The aetiology is unknown but there are many postulated theories. We present a case of an idiopathic gastric rupture involving the greater curvature of 6-week-old boy with incidental findings of being asplenic.